Dissonant Heritage: A Comprehensive Analysis of Local Voices, Perceptions, and Challenges in the Development of Dark Tourism in Muynak - Allaberganov, Azizbek; Justus Liebig University Giessen (My University, 2025)
This dissertation investigates the development of dark tourism in the town of Muynak following the environmental disaster of the Aral Lake. It explores how Muynak transformed into a dark tourism destination, the perceived impacts of this development on local communities, the challenges associated with dark tourism, and the extent to which residents support its further growth. An exploratory sequential mixed-methods design was employed, combining qualitative interviews with experts and stakeholders, quantitative surveys of local residents, as well as informal interviews and field observations to provide contextual insights. Findings reveal that Muynak has gradually transitioned from a leisure-oriented tourism destination to a dark tourism site. Economic and environmental benefits were particularly significant, whereas socio-cultural impacts were comparatively modest. Despite the presence of challenges, local communities generally support further dark tourism development due to its positive economic and environmental outcomes. The study offers both practical and theoretical implications for policymakers and businesses, highlighting strategies to enhance benefits, address challenges, and promote sustainable, community-oriented tourism development.
Keywords: ddc:330; ddc:950